Mechanism of ion flow generation in vacuum arcs; Journal of Experimental and Theoretical Physics; Vol. 93, № 5 - Barengolts S. A.; Mesyats G. A. Gennady Andreyevich; Shmelev D. L. (2001, 2001)
В фонде НТБ ТПУ отсутствует